PEMANFAATAN POTENSI BIJI RAMBUTAN SEBAGAI INOVASI SUMBER PANGAN KRIPIK EMPING PADA MASYARAKAT DESA KERASAAN II: PEMANFAATAN POTENSI BIJI RAMBUTAN SEBAGAI INOVASI SUMBER PANGAN DI PERKEBUNAN KERASAAN II - Dwi Febrianti; Fatimah Zahara Siregar; Syaiful Azhar; Wirdah Millatul Hanifah; Wanda Diana (Politeknik Negeri Sriwijaya, 2021)
The need for food supply for human life has an impact on food resources which are increasing over time. As one of the efforts that can be done by utilizing local potential that can be processed as food products that can be done as a solution to the abundance of existing potential. Utilization of rambutan seeds (Nephelium sp) as processed emping chips which are favored by everyone, generally as snacks. The method used in this activity is in the form of training carried out in KKN DR activities with the main target being the community at the Sipef Kerasa II Plantation, Pematang Bandar District. The purpose of this activity is as a form of educational training for residents in processing rambutan seeds as chips which can later be developed and marketed by the wider community. The results of this training are expected to provide knowledge and briefings for residents in the use of rambutan seeds, which are quite abundant, which were not initially utilized to become a commodity of economic value.